2008
DOI: 10.1117/12.761705
|View full text |Cite
|
Sign up to set email alerts
|

Remote simultaneous dual wavelength imaging photoplethysmography: a further step towards 3-D mapping of skin blood microcirculation

Abstract: This paper presents a camera-based imaging photoplethysmographic (PPG) system in the remote detection of PPG signals, which can contribute to construct a 3-D blood pulsation mapping for the assessment of skin blood microcirculation at various vascular depths. Spot measurement and contact sensor have been currently addressed as the primary limitations in the utilization of conventional PPG system. The introduction of the fast digital camera inspires the development of the imaging PPG system to allow ideally non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 10 publications
0
18
0
1
Order By: Relevance
“…Our previous work demonstrated that this technology offers significant advantage over other blood perfusion scanning techniques, since there are evidences showing a viability of a low-cost iPPG system utilising a conventional web-camera [4] . Simultaneous monitoring of perfusion at different tissue depth using dualwavelength light source was also reported [5] , which could lead to the potential of non-contact 3D mapping of microcirculation. To date, however, iPPG has not found major appreciation in certified medical applications, despite numerous literature reviews of its clinical value and validity.…”
Section: Imaging Ppgmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous work demonstrated that this technology offers significant advantage over other blood perfusion scanning techniques, since there are evidences showing a viability of a low-cost iPPG system utilising a conventional web-camera [4] . Simultaneous monitoring of perfusion at different tissue depth using dualwavelength light source was also reported [5] , which could lead to the potential of non-contact 3D mapping of microcirculation. To date, however, iPPG has not found major appreciation in certified medical applications, despite numerous literature reviews of its clinical value and validity.…”
Section: Imaging Ppgmentioning
confidence: 99%
“…In order to create such evenly distributed light flux at distances greater than 50 cm from a target area, the illuminator is usually constructed using an array of individual LEDs, which has been reported in our previous work [5] [9] , as well as in [10] . One obvious yet underestimated disadvantage of this approach is inevitable spectral variation between individual LEDs even within the same production batch, with a typical value of around 20-40 nm.…”
Section: Light Sourcementioning
confidence: 99%
“…6 Furthermore, we have previously presented an integrated imaging PPG setup for the detection of tissue optophysiological properties. 11 Recent progress in iPPG research activities has stimulated our interest in the remote assessment of the cardiovascular system for evaluation of the influence of exercise.…”
Section: Introductionmentioning
confidence: 99%
“…The feasibility of the camera-based PPG system has been previously demonstrated by means of blood perfusion visualization [6,7] . A previous research report [8] presents a remote reflection-mode CMOS camera-based system with a ring light of similar wavelengths (660 and 840 nm) capturing "heart cycle-related" pulsatile variations.…”
Section: Introductionmentioning
confidence: 99%